Conservative short-term treatment of non-cirrhotic non-malignant portal vein thrombosis - Bošković-Sekulić Jelena; Sekulić Igor; Rančić Nemanja; Stanić Mina; Jovićević Miloš; Perišić Nenad (Vojnosanitetski Pregled)
Introduction. Portal vein (PV) thrombosis (PVT) is a partial or complete obstruction of blood f low as a result of a thrombus mass in the lumen of PV. In the acute phase, the symptoms such as right upper quadrant pain, nausea, and fever are unspecific. A diversity of subacute and chronic symptoms is associated with complications related to PVT and portal hypertension. Case report. A 50-year-old female was admitted to the hospital due to acute abdominal cramping pain. The pain lasted for 15 to 20 min and was followed by defecation of normal stool and hematochezia on three occasions. The abdominal pain recurred after several hours, again followed by hematochezia and tenesmus every 10 min. After admission, a colonoscopy was performed, and it revealed vulnerable, erythematous mucosa of the colon with contact bleeding from the lienal flexure to the rectosigmoid junction. During the colonoscopy, a biopsy was performed. A computed tomography (CT) scan revealed partial PVT of intrahepatic branches of PV, and thrombosis of the inferior mesenteric vein. After conservative treatment with low molecular weight heparin (LMWH) and other supportive measures, the digestive bleeding ceased, and defecation became normal. During the one-month follow-up, the patient had no complications, and the control CT scan revealed normal PV flow without thrombosis. Conclusion. Although rare, a non-malignant and non-cirrhotic PVT should not be neglected in the differential diagnosis because timely and vigilant therapy with LMWH can lead to complete resolution without serious complications.